Prevalence of, and risk factors for, presenting visual impairment: findings from a vision screening programme based on UK NSC guidance in a multi-ethnic population. (October 2018) - Bruce, Alison; Santorelli, Gillian; Wright, John; Bradbury, John; Barrett, Brendan; Bloj, Marina; Sheldon, Trevor
Abstract Purpose To determine presenting visual acuity levels and explore the factors associated with failing vision screening in a multi-ethnic population of UK children aged 4–5 years. Methods Visual acuity (VA) using the logMAR Crowded Test was measured in 16, 541 children in a population-based vision screening programme. Referral for cycloplegic examination was based on national recommendations (>0.20logMAR in one or both eyes). Presenting visual impairment (PVI) was defined as VA >0.3logMAR in the better eye. Multivariable logistic regression was used to assess the association of ethnicity, maternal, and early-life factors with failing vision screening and PVI in participants of the Born in Bradford birth cohort. Results In total, 2467/16, 541 (15%) failed vision screening, 732 (4.4%) had PVI. Children of Pakistani (OR: 2.49; 95% CI: 1.74–3.60) and other ethnicities (OR: 2.00; 95% CI: 1.28–3.12) showed increased odds of PVI compared to white children. Children born to older mothers (OR: 1.63; 95% CI: 1.19–2.24) and of low birth weight (OR: 1.52; 95% CI: 1.00–2.34) also showed increased odds. Follow-up results were available for 1068 (43.3%) children, 993 (93%) were true positives; 932 (94%) of these had significant refractive error. Astigmatism (>1DC) (44%) was more common in children of Pakistani ethnicity and hypermetropia (>3.0DS) (27%) in white children (Fisher's exact, p < 0.001). Conclusions A high prevalence of PVI is reported. Failing vision screening and PVI were highly associated with ethnicity. The positive predictive value of the vision screening programme was good, with only 7% of children followed up confirmed as false positives.